Test of Borax and Formalin on Snacks with Turmeric and Dragon Fruit Extracts at SMAN 1 Nguter, Sukoharjo - Avivi Nida; Farhah Qurrotu 'Aini; Sardjoko Agus Wiyono; Suwarto (Jurnal Biologi Tropis, 2023)
Chemicals such as formalin and borax are actually chemicals that can only be used for purposes outside the body, meaning that borax and formalin are not allowed to enter the human body because they will seriously damage the organs inside. The purpose of this study was to determine the presence of formaldehyde and borax in snacks at SMAN 1 Nguter, Sukoharjo. This research method is experimental research then summarizes the entire research. This study used turmeric and dragon fruit extracts as research indicators. The results of several samples that the researchers observed contained formalin, namely sausage tempura, middle star tempura, bread tempura, rolled noodle tempura, star tempura, cireng tempura, thigh tempura, round white tempura. And some of the samples contained borax, namely ice doger and tempura bintang tengah. Based on the results of the study, it was found that there is a danger posed when consuming foods containing a lot of borax and formalin, one of which can damage liver and kidney function and can even trigger cancer.